2004
DOI: 10.1523/jneurosci.0901-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Absence of C1q Leads to Less Neuropathology in Transgenic Mouse Models of Alzheimer's Disease

Abstract: C1q, the recognition component of the classical complement activation pathway, is a multifunctional protein known to be expressed in brain of Alzheimer's disease (AD) patients. To experimentally address the role of C1q in AD, a mouse model lacking C1q (APPQϪ/Ϫ) was generated by crossing Tg2576 animals (APP) with C1q-deficient mice. The pathology of APPQϪ/Ϫ was compared with that of APP mice and B6SJL controls at 3-16 months of age by immunohistochemistry and Western blot analysis. At younger ages (3-6 months),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
265
4
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 294 publications
(282 citation statements)
references
References 68 publications
12
265
4
1
Order By: Relevance
“…Consistent with a previous report showing decreased MAP2 immunoreactivity in the hippocampus of APP/PS1 mice (Fonseca et al, 2004), our semiquantitative results showed that the vehicle-treated APP/PS1 mice had a dramatic decrease (50%) in MAP2 reactivity in the pyramidal neurons of the CA1 region of the hippocampus compared with the vehicle-treated wild-type controls (Fig. 6 A, B).…”
Section: Atra Treatment Attenuates Neurodegeneration In App/ps1 Micesupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with a previous report showing decreased MAP2 immunoreactivity in the hippocampus of APP/PS1 mice (Fonseca et al, 2004), our semiquantitative results showed that the vehicle-treated APP/PS1 mice had a dramatic decrease (50%) in MAP2 reactivity in the pyramidal neurons of the CA1 region of the hippocampus compared with the vehicle-treated wild-type controls (Fig. 6 A, B).…”
Section: Atra Treatment Attenuates Neurodegeneration In App/ps1 Micesupporting
confidence: 92%
“…Neuronal degeneration and loss observed in the brains of AD patients (West et al, 1994) and in the brains of APP/PS1 transgenic mice (Fonseca et al, 2004;Rutten et al, 2005) is hypothesized to be exacerbated by an inflammatory reaction (McGeer and McGeer, 1999). Given the inhibitory effect of ATRA on glial activation, an indicator of CNS inflammation, we determined the effect of ATRA on neuronal integrity.…”
Section: Atra Treatment Attenuates Neurodegeneration In App/ps1 Micementioning
confidence: 99%
“…C1q components have also previously been suggested to be produced by injured or stressed neurons, especially in Alzheimer's disease (36)(37)(38)(39)(40). Furthermore, deletion of C1q has been shown to reduce pathological signs in APP-transgenic Alzheimer-mice (41). In light of the recent finding that a proportion of mutant SOD1 may be secreted (42), as well as liberated by cell death, and therefore could act from outside the motor neurons, it is tempting to speculate that the induced complement system might recognize such extracellular, misfolded mutant SOD1 and mark the motor neuron for attack by immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…Postsynaptic deficits of PSD95, GluR1, and MAP-2 described in brains from AD patients and Tg2576 mice (Almeida et al, 2005;Fonseca et al, 2004;Liu et al, 2005) may contribute to synaptic dysfunction with resultant impaired learning. In agreement with that, we observed reduced expression of AMPA receptor subunit GluR1, PSD95, and MAP-2 in Tg2576 hippocampus that may contribute to poor performance in the water maze.…”
Section: Discussionmentioning
confidence: 99%